2010
DOI: 10.1371/journal.pone.0009120
|View full text |Cite
|
Sign up to set email alerts
|

Is the Relationship between Body Size and Trophic Niche Position Time-Invariant in a Predatory Fish? First Stable Isotope Evidence

Abstract: Characterizing relationships between individual body size and trophic niche position is essential for understanding how population and food-web dynamics are mediated by size-dependent trophic interactions. However, whether (and how) intraspecific size-trophic relationships (i.e., trophic ontogeny pattern at the population level) vary with time remains poorly understood. Using archival specimens of a freshwater predatory fish Gymnogobius isaza (Tanaka 1916) from Lake Biwa, Japan, we assembled a long-term (>40 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
59
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(64 citation statements)
references
References 36 publications
4
59
0
Order By: Relevance
“…Some researchers have demonstrated that changes in the diet during the ontogenetic development may result in alterations in trophic relationships both at population and species level (Nakazawa et al 2010). The native H. sp2 showed a significant difference in δ 15 N values between juveniles and adults although they are in the same trophic level.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have demonstrated that changes in the diet during the ontogenetic development may result in alterations in trophic relationships both at population and species level (Nakazawa et al 2010). The native H. sp2 showed a significant difference in δ 15 N values between juveniles and adults although they are in the same trophic level.…”
Section: Discussionmentioning
confidence: 99%
“…The PPMR measures the body mass ratio of interacting predators and prey. Body size can be linked with interaction strength, which allows us to describe food webs mediated by size-dependent predation (Brose 2010;Nakazawa et al 2011). In this review, body size represents individual size, including the concept of age or developmental stage, rather than species-specific representative body size, because this review concerns the community consequences of ontogenetic growth.…”
Section: Introductionmentioning
confidence: 99%
“…This represents the simplest possible scenario (i.e., trophic module) for a stage-structured community. However, the concept applies to various community contexts, such as aquatic food webs, in which ontogenetic diet shifts of predatory fish from planktivore to benthivore couple energy flows in the surface and bottom waters (Nakazawa et al 2010, Briones et al 2012, plant-insect interactions, in which stage structures entangle herbivory and pollination networks (Altermatt and Pearse 2011;Ke and Nakazawa, unpublished data), and interface areas, in which metamorphosis of amphibians or aquatic insects connect aquatic and terrestrial ecosystems (Baxter et al 2005;Nakazawa 2015b). …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations